Ta'wil mukhtalif al-hadith: an annotated translation - Bahari, Che Amnah (IIUM Press, 2009)
TA’WIL MUKHTALIF AL-HADITH: AN ANNOTATED TRANSLATION is a work of translation of an Arabic text into English. This text is worthy to be translated because it deals with the needs to understand and appreciate (1) the reason behind the citation of the hadith of the Prophet, (2) the dynamism of the context of the hadith of the Prophet, (3) the correct and proper method of hadith interpretation and (4) the method of contextualizing the hadith of the Prophet in the contemporary life.